Successful closure of gastrocolic fistula using preoperative localization with charcoal nanoparticles tattooing - Nan Lin; Zhicong Cai; Weijin Yang; Youxu Zhou; Yu Wang (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Lin N, Cai Z, Yang W, Zhou Y, Wang Y. Successful closure of gastrocolic fistula using preoperative localization with charcoal nanoparticles tattooing. Turk J Gastroenterol 2018; 29: 252-3.